Securing Bird Feeders from Florida Black Bears - Ethan T. Noel; Elizabeth F. Pienaar (EDIS)
The Florida black bear (Ursus americanus floridanus) is the only species of bear in Florida, with an estimated population of approximately 4,030 bears. Bears are excellent climbers and can access bird feeders that are suspended from trees. This 3-page fact sheet explains how to secure bird seed from bears so that they don’t become reliant on human food sources, a condition that puts them at greater risk of being killed from vehicle collisions, illegal shooting, or euthanasia. Written by Ethan T. Noel and Elizabeth F. Pienaar, and published by the Wildlife Ecology and Conservation Department, March 2017.